D : (a tale of two worlds) : a novel - Faber, Michel (Hanover Square Press, 2020)
Baffled by the sudden disappearance of the letter D, a young woman is summoned to the home of a former history teacher before arriving in an enslaved, wintry land where free thinking is under threat.